Przepis kulinarny w perspektywie nadawcy z dysfunkcją słuchu — tekstowe aktualizacje wzorca gatunkowego - Jachimowska, Katarzyna (Acta Universitatis Lodziensis. Folia Linguistica, 2017)
In the article the author draws the attention to use of the prototype of the recipe by the hearing impaired persons. The departures from the prototype on the structural level as well as language deformations were observed. The texts were also analysed from the perspective of Polish sign language interferences with Polish language. Analysis of the material allowed to make conclusions related to genology competencies of hearing impaired persons. In most cases the characteristics of the prototype were met. The language deformations and language errors did not obscure the text purpose. The analyses indicated that the pathological application of the prototype on the stylisticlexical level does not lead into communication failure as long as the prototype was applied in the structural, cognitive and pragmatic aspects.